2015
DOI: 10.1248/bpb.b14-00780
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Attenuates Doxorubicin-Induced Cytotoxicity to MCF-7 Human Breast Cancer Cells

Abstract: Luteolin, a flavone found in some vegetables, has been reported to exhibit antioxidant, antiinflammatory, and anticancer activities. In the present study, we found that luteolin has biphasic effects on the viability of the human breast cancer cell line MCF-7. That is, cell viability increased at relatively low luteolin concentrations and decreased at relatively high concentrations. Focusing on the proliferative effect at low concentrations, we showed that luteolin has a cytoprotective effect on MCF-7 cells whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…For example, luteolin has been shown to induce cell cycle arrest and apoptosis, inhibit proliferation and metastatic progression, and attenuate doxorubicin-induced cytotoxicity [3, 7, 20, 22]. Although luteolin could inhibit proliferation and induce cell apoptosis in the HCC cell line HepG2 [11, 12], its role in regulating autophagy, and the relationship between cell apoptosis and autophagy, has not been elucidated in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, luteolin has been shown to induce cell cycle arrest and apoptosis, inhibit proliferation and metastatic progression, and attenuate doxorubicin-induced cytotoxicity [3, 7, 20, 22]. Although luteolin could inhibit proliferation and induce cell apoptosis in the HCC cell line HepG2 [11, 12], its role in regulating autophagy, and the relationship between cell apoptosis and autophagy, has not been elucidated in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Plants rich in luteolin have been used in Chinese traditional medicine to treat various diseases, such as hypertension, inflammatory disorders, and cancer [3, 4]. The anti-cancer activities of luteolin have been demonstrated in many cancer cells, such as pancreatic cancer, prostate cancer, breast cancer, colorectal cancer, and ovarian cancer [5-8].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have been focusing on Chinese herb extracts, with certain compounds recently reported as molecular targeted anti-cancer drugs, such as luteolin, a novel inhibitor of RSK. Luteolin has been the focus of clinical-translational interest in anticancer treatment (31)(32)(33). In the present study, the effects of pharmacological inhibition of the RSK1 inhibitor, luteolin, on leukemic cell lines were investigated.…”
Section: A B C D Ementioning
confidence: 99%
“…Along with its antioxidant and anti‐inflammatory properties, luteolin has demonstrated anticancer effects in a variety of types of cancer through several mechanisms including inducing cell death, slowing cell proliferation and halting cell growth. Several studies have shown that luteolin down‐regulates Akt phosphorylation in gastric, breast, brain and other cancer cell lines .…”
mentioning
confidence: 99%